Methodological Framework for Training Future Primary School Teachers Using Art Technologies (Gumilyov Journal of Pedagogy, 2026)
This article examines the issue of professional training of future primary education teachers based on art technologies. To this end, the concepts of “professional training” and “art technologies” are clarified, and a content analysis of the concept of art technologies is conducted. Based on an analysis of scientific, pedagogical, and psychological literature, the main directions of professional training of future primary education teachers through art technologies are identified. In accordance with these directions, the components, criteria, and indicators of professional training, as well as the characteristics of training levels of future primary education teachers based on art technologies, are defined. The effectiveness of art technologies in the professional training of future primary education teachers is theoretically substantiated, and on this basis, a pedagogical experiment plan is developed, including diagnostic and formative stages. The experiment involved graduating students. At the diagnostic stage, a diagnostic questionnaire, practical situations, and practical tasks were developed. The quantitative data obtained at this stage were systematized, leading to the conclusion that the participants’ levels were comparable and required improvement. To improve the results, an “ART” student club program was designed and implemented during the formative experimental stage. The program included various forms of activities, such as competitions and seminars; role-playing, verbal, and creative exercises aimed at releasing creative energy; content-related tasks; speech development contests; the use of show technologies; and the creation of a YouTube channel. As a result, the study concludes that the use of art technologies is effective in the professional training of future primary education teachers.